REGULATION 28 OF THE PENSION FUNDS ACT: REGULATING PRUDENTIAL INVESTMENT (The Pretoria Student Law Review, 2021)
On 23 February 2011, the Minister of Finance, Pravin Gordhan, announced that there would be changes made to Regulation 28 of the Pension Funds Act (the 1998 regulation). In terms of this amendment, the objectives of the new regulation would be to ensure that contributions made by South Africans towards their retirement savings would be invested in a prudent manner that would not only protect the investor but would also be geared towards economic growth and development. The idea of protecting retirement savings was first introduced into South African law in 1962 through the promulgation of Regulation 28 (the 1962 regulation). Due to vast changes in the market structure at the time, the 1962 regulation had to be revised. The beginning of 1998 saw the updated version of Regulation 28 come into force in terms of Section 36(1)(bB) of the Pension Funds Act. It had therefore undergone a major revision to bring it more in line with other regulations and with the ever-changing investment environment; but this would not be the only change Regulation 28 would undergo.
Keywords: Regulation 28 of the Pension Funds Act; retirement savings; investment; economic growth and development